ZIF-90 nanoparticles modified with a homing peptide for targeted delivery of cisplatin - Abubakar, Adamu; Abdulmalek, Emilia; Wan Ibrahim, Wan Norhamidah; Cordova, Kyle E.; Abdul Rahman, Mohd Basyaruddin (Frontiers Research Foundation, 2022)
To improve the selective delivery of cisplatin (Cis) to cancer cells, we report and establish the significance of active, targeting drug delivery nanosystems for efficient treatment of lung cancer. Specifically, pH-responsive nano-sized zeolitic imidazolate framework (nZIF-90) was synthesized, post-synthetically modified with an Arg-Gly-Asp peptide motif (RGD@nZIF-90), a known cancer cell homing peptide, and loaded with a large amount of Cis (RGD@Cis⊂nZIF-90). RGD@Cis⊂nZIF-90 was shown to be highly stable under physiological conditions (pH = 7.4) with framework dissociation occurring under slightly acidic conditions (pH = 5.0)–conditions relevant to tumor cells–from which 90% of the encapsulated Cis was released in a sustained manner. In vitro assays demonstrated that RGD@Cis⊂nZIF-90 achieved significantly better cytotoxicity (65% at 6.25 μg ml−1) and selectivity (selectivity index = 4.18 after 48 h of treatment) against adenocarcinoma alveolar epithelial cancer cells (A549) when compared with the unmodified Cis⊂nZIF-90 (22%). Cellular uptake using A549 cells indicated that RGD@Cis⊂nZIF-90 was rapidly internalized leading to significant cell death. After successfully realizing this nanocarrier system, we demonstrated its efficacy in transporting and delivering Cis to cancer cells.